Learning from Failure: A case study on creative problem solving - Sousa, F. (2014)
to learn even from failure. With the goal of increasing efficiency by reducing session time and also due to theoretical considerations, a four-step model was designed, comprising the stages of objective-finding, problem-definition, action-planning and the action itself. Following these adaptations, our research involved an organisation that enabled us to bring managers and volunteers to work on a project. The organisation is the only private museum in the Algarve region of Portugal; it is involved in regional culture and, despite competent management, faces serious financial difficulties. A team of 22 people was established, representing both immediate and remote geographical communities, cultural organisations, and representatives of innovative projects related to the hospitality industry. From the interventions, and the follow up procedures, we learned that some project failures could have been problem. The analyses and conclusions allowed the development of principles that will be applied in future interventions, giving rise to improvements in the facilitation process, bringing in important implications for developing collaboration between organizations. Team composition and the handling of client-team relationships seem to be promising areas for research, given their potential